The Role of Kiai Leadership in the Management of Al Azhar Menganti Gresik Islamic Boarding School in the Global Era - Ahmad Muthi’Uddin; Babun Suharto; Ahmad Qoni Dewantoro; Titiek RH (Penerbit Hellow Pustaka, 2026)
The development of globalization brings significant challenges for Islamic educational institutions, including Islamic boarding schools. Social, economic, and technological changes require Islamic boarding schools to adapt without abandoning the traditional values that are their identity. This study aims to analyze the role of kiai leadership in the management of Al Azhar Menganti Gresik Islamic Boarding School in the global era. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Research informants included kiai caretakers, pesantren managers, and ustadz. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that kiai leadership plays a strategic role in maintaining the balance between pesantren values and the demands of globalization through strengthening institutional vision, participatory decision-making, and developing adaptive pesantren management. Kyai leadership is a key factor in maintaining the sustainability and competitiveness of pesantren in the global era.